Respostas

2013-09-05T22:43:56-03:00
X²+3x-4 = 0
delta = b²-4.a.c
delta = 3²-4.1.(-4)
delta = 9+16
delta = 25

-b+- raiz de delta
----------------------
             2.a

-3+- raiz de 25
--------------------
           2.1
-3+- 5
--------
    2
x' = -3+5  
      ------- = 2 
          2      ---- = 1
                    2

x" = -3-5
      ------- = -8
          2      ------ = -4
                    2

x' = 1
x" = -4
1 5 1
2013-09-05T22:58:14-03:00
X2 + 3x -4 = 0 (a=1,b=3, c=-4)
> b2 -4.a.c
> 3 ao quadrado -4.1.(-4)
> 9 + 16 = 25

x' = -b + ou - raiz de 25 / 2.a

-3 + 5 / 2 = +2 / 2 = 1

x" = -b + ou - raiz de 25 / 2a

-3 -5 / 2 = -8 / 2 = -4

Espero que tenha ajudado!!!